2011
DOI: 10.1093/nar/gkr679
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of the BRCA1 transcriptome through microarray and ChIP-chip analysis

Abstract: A role for BRCA1 in the direct and indirect regulation of transcription is well established. However, a comprehensive view of the degree to which BRCA1 impacts transcriptional regulation on a genome-wide level has not been defined. We performed genome-wide expression profiling and ChIP-chip analysis, comparison of which revealed that although BRCA1 depletion results in transcriptional changes in 1294 genes, only 44 of these are promoter bound by BRCA1. However, 27% of these transcripts were linked to transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
47
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 43 publications
2
47
0
Order By: Relevance
“…47 The ZF5 motif was found to colocalize with BRCA1 in humans and c-myc in mice. 48,49 To date, the relationship between TESC and BRCA1 or C-MYC in humans is still unknown. It has also remained unclear if TESC upregulation might occur in patients who developed drug resistance to newer and more specific FLT3 inhibitors like midostaurin and quizartinib.…”
Section: Discussionmentioning
confidence: 99%
“…47 The ZF5 motif was found to colocalize with BRCA1 in humans and c-myc in mice. 48,49 To date, the relationship between TESC and BRCA1 or C-MYC in humans is still unknown. It has also remained unclear if TESC upregulation might occur in patients who developed drug resistance to newer and more specific FLT3 inhibitors like midostaurin and quizartinib.…”
Section: Discussionmentioning
confidence: 99%
“…For example, dynamic GRN studies in plants have uncovered genome-wide responses that occur within as little as 3 min following a nitrogen (N) nutrient signal perturbation (1). However, many of the underlying rapid and temporal network connections between transcription factors (TFs) and their targets elude detection even in fine-scale time-course studies (2,3), as current methods, such as chromatin immunoprecipitation (ChIP), require stable TF binding in at least one time point to identify primary targets (4)(5)(6). However, recent models suggest that GRNs built solely on TF binding data are insufficient to recapture transcriptional regulation (7)(8)(9).…”
mentioning
confidence: 99%
“…However, recent models suggest that GRNs built solely on TF binding data are insufficient to recapture transcriptional regulation (7)(8)(9). Compounding this dilemma, TFs have been found to stably bind to only a small percentage (5-32%) of the TF-regulated genes across eukaryotes (4)(5)(6)(10)(11)(12)(13). Because TF binding is required to define the primary targets in current GRN studies, the large set of TFregulated but not TF-bound genes must be categorically dismissed as indirect or secondary targets (4,5,(11)(12)(13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We found that cells depleted of BRCA1 or BRCA2 demonstrate genome instability, even without DNA damage (64,65). BRCA1 and BRCA2 are transcriptional coregulators, and genomic studies have defined promoter binding (66,67). Because BRCA1 and BRCA2 are tumor suppressors, it may be postulated that increased transcriptional activity of oncogenes is one basis for carcinogenic effects following mutations causing loss of function of the BRCA1 or BRCA2 protein.…”
Section: Tumor Suppressors: Brca1 and Brca2mentioning
confidence: 91%